Agronomic performance and chemical composition of genotypes and cultivars of Megathyrsus maximus in Roraima’s savannas (Research, Society and Development, 2022)
The agronomic performance of 23 genotypes and six commercial cultivars of Megathyrsus maximus was evaluated under natural field conditions at the Roraima´s savannas, during the period of June 2015 to September 2019. The evaluated parameters were green dry matter (GDM) yield, leaf, stem and dead DM yields, crude protein (CP) contents, concentrations of neutral detergent fiber and acid detergent fiber. The genotypes and cultivars evaluated affected the yields and the chemical composition of the forage. The most promising genotypes showed superior agronomic performance than the commercial cultivars evaluated. The genotypes B16; PM10; PM40 and PM14 showed the highest green dry matter yields and forage with better nutritional quality, higher CP and lower fiber contents. These showed average yields of 5,103 and 3,925 kg ha-1, for green DM and leaf DM, respectively, which represented increments of 20.7 and 12.8%, compared with those registered for the commercial cultivars. The genotype PM15 evidenced the highest productive performance during the dry season, constituting an option for regions with climatic restrictions, notably reduced rainfall. All genotypes and cultivars showed seasonal growth. The genotypes that showed the best seasonal distribution of forage production were PM11, PM36, PM30 and PM33, which provided 47.9; 46.8; 41.0 and 40.7% of GDM production during the dry season. In general, higher crude protein and lower fiber contents were directly correlated with the percentage of leaves in the available forage. The evaluated genotypes presented great genetic variability for the accumulation of forage and its chemical composition that can subsidize the generation of new commercial cultivars.